The Creation of A Tourism Photo Spot For Seribu Cemara Beach in An Effort To Improve The Tourism Economy and Tourist Attraction - Ramadani, Gilang (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2024)
One of the most important assets that must be possessed in order to increase and develop tourist attractions is the attractiveness of tourist objects. To increase tourist visits to the holiday destination Seribu Cemara Beach, Seruyan Hilir Timur, the 2023 Group 8 Community Service Program at the Palangka Raya State Islamic Institute is increasingly working with village officials to add photo spots in holiday destination areas. Ideally, the existence of this photo spot will increase tourist visits so that it will have an impact on increasing regional income obtained from entrance tickets and stops. In addition, an increase in visitors will have an impact on the income of local traders in Sungai Bakau Village. This community service activity uses PAR (Participatory Action Research), which examines location requirements for community service and participation. In general, this movement was effectively carried out by inviting residents to take part in making photo spots to add to the attractiveness of holiday destinations.